Rule of Law and Human Mobility in the Age of the Global Compacts - Panizzon, Marion; Vitiello, Daniela; Molnar, Tamas (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This is a reprint of the Special Issue The Rule of Law and Human Mobility in the Age of the Global Compacts: Relativising the Risks and Gains of Soft Normativity?, which hosts nine contributions that critically dive in the normative, administrative, and judicial obstacles and potential standing of the legal framework and implementation setting of the Global Compact for Safe, Orderly, and Regular Migration (GCM) and the Global Compact for Refugees (GCR). The following four thematic clusters are proposed: 1. The justiciability of the actionable commitments under the Global Compacts before domestic courts as a threshold for the degree of judicial protection for migrants and refugees; 2. How human rights treaties and the Global Compacts are connected might matter for the level of rights protection; 3. Externalized migration policies and border management as a threat for the regional scope of human rights and as a risk factor for the rule of law; and 4. Data-driven and evidence-based migration policies, including digital technology as facilitators for standardizing migration and asylum decisions. By inquiring into human rights protection at the boundaries of the political commitments under the Global Compacts, this reprint engages in a conversation about the confinements that migrants and refugees encounter when accessing their substantive and procedural rights and encourages legal science/scholars to map an emerging field of study within global migration governance.